Dry Eye Post-Laser-Assisted In Situ Keratomileusis: Major Review and Latest Updates - Eyal Cohen; Oriel Spierer (Journal of Ophthalmology)
Dry eye is one of the most common complications occurring after laser-assisted in situ keratomileusis (LASIK), with virtually all patients experiencing some degree of postoperative dry eye symptoms. Enhanced understanding of the pathophysiology and mechanism of dry eye development in addition to preoperative screening of patients who are prone to dry eye is essential for better patient satisfaction and for improving short-term visual outcome postoperatively. This article reviews the latest studies published on LASIK-associated dry eye, including epidemiology, pathophysiology, risk factors, preoperative assessment, and management.